2014
DOI: 10.1371/journal.pone.0108006
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Cell Proliferation Using Water Dispersible Germanium Nanowires

Abstract: Group IV Nanowires have strong potential for several biomedical applications. However, to date their use remains limited because many are synthesised using heavy metal seeds and functionalised using organic ligands to make the materials water dispersible. This can result in unpredicted toxic side effects for mammalian cells cultured on the wires. Here, we describe an approach to make seedless and ligand free Germanium nanowires water dispersible using glutamic acid, a natural occurring amino acid that alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A recent study has shown the biocompatibility of SiC/SiO 2 NWs according to a cell viability assay (A549, HuDe, MCF‐7, and THP‐1 cells) . When germanium NWs were applied to L929 cells, an increase in cell proliferation was recorded using MTT and WST‐1 assays and by quantifying the number of cells . In contrast, another report has demonstrated that β‐SiC NWs induce apoptosis due to oxidative stress in MC3T3‐E1 cells after 48 h exposure to NWs, even though their cell viability remains high after 24 h exposure (MTT assay) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown the biocompatibility of SiC/SiO 2 NWs according to a cell viability assay (A549, HuDe, MCF‐7, and THP‐1 cells) . When germanium NWs were applied to L929 cells, an increase in cell proliferation was recorded using MTT and WST‐1 assays and by quantifying the number of cells . In contrast, another report has demonstrated that β‐SiC NWs induce apoptosis due to oxidative stress in MC3T3‐E1 cells after 48 h exposure to NWs, even though their cell viability remains high after 24 h exposure (MTT assay) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cytotoxicity of Ge NPs has been subject to some research over the years. For instance, researchers using MTT and WST-1 assays to measure cell viability in L929 cells upon exposure to Ge NWs observed an increased cell proliferation, concluding that water-soluble wires were non-toxic and biocompatible (Bezuidenhout et al, 2014). However, another study demonstrated that β-silicon carbide (SiC) NWs might induce apoptosis through oxidative stress in MC3T3-E1 cells after an incubation period of 48 h, although the cell viability remained relatively high after 24 h of exposure (MTT assay) (Xie et al, 2014).…”
Section: Studies With Silicon Nanoparticlesmentioning
confidence: 99%
“…14,21,[27][28][29]37 The in vivo animal model provided further toxicity information where 3 out of 9 of the in vivo animal model studies indicated partial nontoxic animal effect, one was toxic while the remaining results recommended ENPBCs as a potential candidate for drug therapy with limited information on toxicity (Table S2). Some of the in vivo ENPBCs toxicity effects demonstrated programmed cell death, causing the release of H 2 S. 29 The ENPBCs that exhibited in vivo nontoxic effect were mostly those that had the therapeutic effects of antibody-drug conjugate, 27 CTAB layers of gold for diagnosing rheumatoid arthritis, 30 surface coating polymeric NPs used for inhibiting cancerous cells 31,[38][39][40][41][42][43][44][45][46][47] and felodipine-loaded polymers for pathological examination of different organs of Wister albino mice 50. The ENPBCs with partial nontoxic effect were chitosan-coated polymers for drug delivery, 49 silver NPs coated polymers that were found localized in various body organs, 48 and drug delivery polymeric NPs for anticancer. 51 The findings indicated limited data and information regarding the regulation of ENPBCs toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the limitations are also prevalent despite a host of other instruments including UV-Vis absorption spectroscopy, TEM, SEM, HrTEM, DLS, HPLC, ICP-MS, FTIR, and AFM for characterizing ENPBCs properties, 9 as listed in Table S1. 14 , 21 - 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation